Finding gaps: An assessment of infection control needs in China - Song, Xiaoyan (International Journal of Infection Control, 2011)
Despite that infection control (IC) practice in China had advanced rapidly, little was known about staffing qualification and status of IC programs. The aim of this study was to describe characteristics of IC professionals (ICPs) and to identify opportunities for improving IC practice in China. A cross-sectional study was conducted by surveying ICPs attending national conferences in 2010. The survey consisted of 17 questions ranged from professional training, years of practices, to educational needs. Eight hundred eighty individuals from hospitals located in 32 of 34 provinces and autonomous regions in China responded to the survey. Of these respondents, 45% had five or more years IC experience. Their professional education included nursing (59.2%), medicine (31.6%), and public health (8.8%). Hand hygiene (81%), prevention of multi-drug resistant organisms (60%), and outbreak management (53%) were considered top priorities. Respondents primarily relied on results of the bi-annual prevalence study conducted in their hospitals and personal experience to determine priorities and risks of healthcare associated infections (HAIs). Staff collaboration (81.5%) and leadership support (61.0%) were viewed as the most important factors contributing to successes of HAI prevention. Nearly all (95.6%) respondents favoured more continuing education.This study revealed that China had highly trained and experienced ICPs, but it remained critical to empower them to practice evidence-based IC. Focused training could be one of effective means to achieve the goals.